PELAYANAN CUSTOMS CLEARANCE PADA PERUSAHAAN FREIGHT FORWARDING - Budi Purwanto; Hendrik Sabfika; D.A Lasse (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this research is to find out the conformity degree between performance and interests. This research used a survey method with Importance Performance Analysis (IPA) approach. The result shows that the service implementation is already good enough. Based on Cartesian Coordinate Analysis, there are two factors of service which have not met customer expectations in Quadrant A yet; punctuality in shipping goods and staff as the problem solver. The two factors become main priorities of the company. While in Quadrant B, there are three factors of company achievement that need to be maintained; customs clearance service fee, employees work thoroughly and detailed with experience, and good office facilities. Quadrant C shows the ability of employees to work smart using concepts; greet and smile, and also give attention to the customers. The last is Quadrant D that shows although customers do not need phone or email assistance anymore, the company still provides them.